Estudo das mesofases líquido-cristalinas através da técnica de elipsometria de emissão - Pereira, Gustavo Gonçalves Dalkiranis (2013)
In present work we studied the processes of phase transition of five luminescent liquid-crystals by using emission ellipsometry technique. The samples studied present different mesophases liquid crystalline between the solid crystalline and liquid isotropic phases. The samples were characterized by optical absorption, photoluminescence, and emission ellipsometry technique (EE) in function of sample temperature. The EE measurement allowed us obtain the Stokes parameters, the degree of polarization of emitted light, and ellipticity and rotation angle of the polarization ellipse. In addition, we founded that the degree polarization, the ellipticity, and the rotation angle of polarization ellipse of emitted light change when the sample temperature increase. It was possible to correlate those changes with the phase transition temperature for each sample in concordance with the literature data. Finally, we propose empirical model to explain our results using the emission ellipsometry technique to determine the phase transition temperature of luminescent liquid crystal systems.